Spectrophotometric Determination of Trifluoperazine hydrochloride in Pharmaceutical Tablets by Oxidative Coupling Reaction with 2, 5-Dimethoxyaniline - Karrar Majeed (Journal of Global Pharma Technology, 2018)
A simple and sensitive spectrophotometric method was developed for the determination of Trifluoperazine hydrochloride (TRF) in pure form and in pharmaceutical tablets. The method was based on oxidative coupling reaction of TRF with 2, 5 dimethoxyaniline to form colored product with maximum absorbance at 722 nm. The reaction conditions were studied and optimized. The linear range for the determination of TRF was 0.1–7 mg mL-1, while the detection limit and quantification limit are 0.018 and 0.061 μg ml-1, the molar absorptivity of 9.240×104 L mol-1cm-1 with Shandell's sensitivity index 0.0051 μg cm-2.The precision and accuracy of the method are checked by calculating relative standard deviation (RSD) (< 0.506%) and average recovery (99. 696%). The value of the stability constant has been calculated and found to be 3.31 ×104 L.mol-1. A statistical comparison of these results with those obtained by the British pharmacopoeia procedure using the Student t-test and variance ratio F-test shows a good agreement and indicates no significant difference in accuracy and precision at the 95% confide.Keywords: Trifluoperazine hydrochloride, 2, 5-dimethoxyaniline, Pharmaceutical tablets, spectrophotometric.